Productivity and trade orientation in UK manufacturing - Marian Rizov; Patrick Paul Walsh (Institute for the Study of Labor (IZA), 2007)
Within a structural model we explicitly allow for the trade orientation of companies to estimate productivity dynamics within 4-digit UK manufacturing industries. We use the FAME data on UK companies over the period 1994-2003. Following Ackerberg et al. (2005) we adjust the algorithm in Olley and Pakes (1996) by augmenting investment and exit decisions to allow for exogenous demand shocks by trade orientation, assuming that labour and capital are state variables, and productivity follows a first-order Markov process. We extend the framework further by allowing exporting to be an additional control variable that is driven by lagged productivity as in Melitz (2003), leading productivity to follow a second-order Markov process. We find that over the period of introduction of the Euro improvements in aggregate productivity were driven by exporters mainly by market share reallocations away from inefficient and towards efficient export companies. Aggregate productivity also benefited from improvements in productivity of non-exporters but was driven by improvements within companies rather than by market share reallocations. In a period of sustained real exchange rate appreciation both export cleansing and competitive pressure on non-exporters seem to have contributed to improvements of productivity in the UK manufacturing.
urn:nbn:de:101:1-20080401229
Keywords: 330; Produktivität; Verarbeitendes Gewerbe; Exportindustrie; Großbritannien